2012
DOI: 10.1037/a0030202
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the “we” in “me” sports: The need to consider individual sport team environments.

Abstract: Most individual sport settings involve groups, as athletes often train in a team environment even though they compete individually and often in opposition to their teammates. Despite the pervasiveness of individual sport, group dynamics research has almost exclusively investigated team sports because team members rely on one another during the competitive group task. However, the reliance on task interdependence to dichotomize sport environments into one of two categories (i.e., team or individual) overlooks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…If this is the case, athletes' responses were in agreement with social interdependence theory (Johnson & Johnson, 2005), which suggests that the structure of group members' reliance on one another (e.g., group outcomes) will guide their interactions and partially determine the influence one individual has on another. Given that group outcomes are present in some individual sports and not in others, these results support the proposition that group outcomes are an important distinguishing feature for sport types (cf., Evans et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…If this is the case, athletes' responses were in agreement with social interdependence theory (Johnson & Johnson, 2005), which suggests that the structure of group members' reliance on one another (e.g., group outcomes) will guide their interactions and partially determine the influence one individual has on another. Given that group outcomes are present in some individual sports and not in others, these results support the proposition that group outcomes are an important distinguishing feature for sport types (cf., Evans et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Correspondingly, Evans, Eys, and Bruner (2012) suggested that the structure of interdependencies relating sport group members will guide the types of interactions between them. For that reason, the authors formed four distinct individual sport team types based on interdependence structures: (a) collective (e.g., a cross country running team where all participants compete in one event and have a collective goal), (b) cooperative (e.g., a track and field team where all participants may not compete in the same event, but still have a collective goal), (c) contrient (e.g., a cross country skiing team, where all participants compete in the same events, but where there is no formal team goal), and (d) independent (e.g., a wrestling team where participants compete in different weight classes and there is no formal team goal).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…One of the dynamic properties that appears to distinguish sport activities is the degree of interdependency required among members for the performance of a task (Evans, Eys, & Bruner, 2012). Furthermore, the categories of team and individual sports are conceptually distinguished based on interdependency, with team sports conceptually requiring a higher degree of collaboration and social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…One of those relates to the prevalence of groups in sport. To be sure, most sports involve the use of groups whether in competition or during training-even individual sport athletes typically practice and compete alongside teammates (e.g., Evans, Eys, & Bruner, 2012). Similarly, although athletic ability is paramount for team success, the dynamics within the team have been found to be of equal consequence (e.g., Carron, Martin, & Loughead, 2012).…”
mentioning
confidence: 97%